Sustainability and Water Management: A technological approach to evaluate water infiltration in different soils - Luis Fernando Fantti; Willian José Ferreira; Marcelo dos Santos Targa; Julio Cesar Raposo de Almeida; Rafael Barbosa Rodrigues; Marcos Cleve da Silva (Revista de Investigación Agraria y Ambiental, 2025)
Context: The assessment of water infiltration in different soil types is of great importance for the sustainable management of water and soil resources. In order to promote sustainable water management practices and maintain soil integrity, it is essential to explore methods that provide accurate measurements and a deeper understanding of these processes.